2001
DOI: 10.1037/0097-7403.27.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Relative validity effects with either one or two more valid cues in Pavlovian and instrumental conditioning.

Abstract: Two experiments investigated the relative validity effect with either 1 or 2 continuously reinforced cues in Wistar rats using appetitive Pavlovian and instrumental preparations. Discrimination training involved 3 compound cues containing a common element (1AX: 1BX: 2CX). In the first true-discrimination group (TD-1), CX was followed by food, but AX and BX were not. In the second true-discrimination group (TD-2), AX and BX but not CX were followed by food. In the third, pseudodiscrimination group (PD), food fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 19 publications
4
34
0
Order By: Relevance
“…Murphy et al (2001a) reported simulations from the Rescorla-Wagner model for differences between the learning rate parameters for reinforcement that were similar to those we report here in Figure 1 for the standard relative validity preparation. The model predicted that TD-1 and TD-2 treatments would have markedly different effects on the associative strength controlled by X.…”
Section: Two-cue Relative Validitysupporting
confidence: 60%
See 3 more Smart Citations
“…Murphy et al (2001a) reported simulations from the Rescorla-Wagner model for differences between the learning rate parameters for reinforcement that were similar to those we report here in Figure 1 for the standard relative validity preparation. The model predicted that TD-1 and TD-2 treatments would have markedly different effects on the associative strength controlled by X.…”
Section: Two-cue Relative Validitysupporting
confidence: 60%
“…Clearly the theory predicts that the difference between TD-1 and TD-2 must be at least of the same magnitude as the difference between TD-2 and PD, and in most cases it is larger. Murphy et al (2001a) reported two experiments using rats to test this prediction. The first experiment used a classical conditioning paradigm in which brief (10-sec) audiovisual stimuli predicted presentations of food pellets.…”
Section: Two-cue Relative Validitymentioning
confidence: 86%
See 2 more Smart Citations
“…When β 1 and β 2 have the same value, the model predicts that X should have the same associative strength in both the correlated and the uncorrelated groups. On the other hand, if β 1 is higher than β 2 , it predicts correctly that X in the uncorrelated group should have more associative strength than in the correlated group (see Murphy, Baker, & Fouquet, 2001, for an extensive discussion). In their original work, Rescorla and Wagner used values of 0.2 for β 1 and 0.1 for β 2 , which would lead to a correct prediction.…”
Section: Introductionmentioning
confidence: 99%